EPCR promotes breast cancer progression by altering SPOCK1/testican 1-mediated 3D growth. Issue 1 (December 2017) - Perurena, Naiara; Zandueta, Carolina; Martínez-Canarias, Susana; Moreno, Haritz; Vicent, Silvestre; Almeida, Ana; Guruceaga, Elisabet; Gomis, Roger; Santisteban, Marta; Egeblad, Mikala; Hermida, José; Lecanda, Fernando
Abstract Background Activated protein C/endothelial protein C receptor (APC/EPCR) axis is physiologically involved in anticoagulant and cytoprotective activities in endothelial cells. Emerging evidence indicates that EPCR also plays a role in breast stemness and human tumorigenesis. Yet, its contribution to breast cancer progression and metastasis has not been elucidated. Methods Transcriptomic status of EPCR was examined in a cohort of 286 breast cancer patients. Cell growth kinetics was evaluated in control and EPCR and SPARC/osteonectin, Cwcv, and kazal-like domains proteoglycan (SPOCK1/testican 1) silenced breast cancer cells in 2D, 3D, and in co-culture conditions. Orthotopic tumor growth and lung and osseous metastases were evaluated in several human and murine xenograft breast cancer models. Tumor-stroma interactions were further studied in vivo by immunohistochemistry and flow cytometry. An EPCR-induced gene signature was identified by microarray analysis. Results Analysis of a cohort of breast cancer patients revealed an association of high EPCR levels with adverse clinical outcome. Interestingly, EPCR knockdown did not affect cell growth kinetics in 2D but significantly reduced cell growth in 3D cultures. Using several human and murine xenograft breast cancer models, we showed that EPCR silencing reduced primary tumor growth and secondary outgrowths at metastatic sites, including the skeleton and the lungs. Interestingly, these effects were independent of APC ligand stimulation in vitro and in vivo. Transcriptomic analysis of EPCR-silenced tumors unveiled an effect mediated by matricellular secreted proteoglycan SPOCK1/testican 1. Interestingly, SPOCK1 silencing suppressed in vitro 3D growth. Moreover, SPOCK1 ablation severely decreased orthotopic tumor growth and reduced bone metastatic osteolytic tumors. High SPOCK1 levels were also associated with poor clinical outcome in a subset breast cancer patients. Our results suggest that EPCR through SPOCK1 confers a cell growth advantage in 3D promoting breast tumorigenesis and metastasis. Conclusions EPCR represents a clinically relevant factor associated with poor outcome and a novel vulnerability to develop combination therapies for breast cancer patients.